PENINGKATAN KOMPETENSI MELAKSANAKAN PENILAIAN PSIKOMOTOR BAGI GURU PJOK SMP MELALUI KEGIATAN WORKSHOP PENILAIAN DI WILAYAH KELOMPOK BINAAN – E KOTA SEMARANG TAHUN 2015 - Sunaryo Prodjo (Jurnal Penelitian Pendidikan, 2015)
This study is based on the lack of competence of Physical Education Sports and Health (PJOK) teachers in psychomotor assessment in the Junior High School Auxiliaries E Semarang. Results of monitoring and evaluation that researchers do regarding to the average teachers of PJOK in target area showed that they were not able to assess psychomotor well. This is evidenced by the absence of documentary proof of psychomotor aspects of the assessment. The issues expected to be addressed through guidance to teachers through assessment workshop. This research aims to improve the competence of PJOK Junior High School teachers in implementing the psychomotor assessment through assessment workshop. This research method is the action research carried out by two cycles. Based on the research results it can be concluded that the action can improve the assessment workshop of PJOK teacher competence in the assessment of students psychomotor amounted to 21.15%. Research recommendations as follows: (1) Workshop can be done by the school supervisor for a number of incompetent teachers who were identified in a matter of learning assessment; (2) In the practical learning of teachers needs to be directed to prepare a measuring instrument properly, making it easy to carry out the psychomotor assessment process; and (3) teachers difficulties in assessing psychomotor need to be supported by the school in terms of funding and financing to attend trainings teaching profession, so that non-education teacher of PJOK can have knowledge and competence in terms of scoring the psychomotor practice in sports.